The Effect Ant-Nest Plant (Myrmecodia pendans) Extract on Streptococcus sanguinis and Treponema denticola Biofilms - Nely Soviati; Armelia Sari Widyarman; Ciptadhi Tri Oka Binartha (Indonesian Dental Association, 2020)
Introduction: Ant-nest plant (Myrmecodia pendans) contains triterpenoid, flavonoid, saponin and tannin that acts as antibacterial substance. Objectives: This study’s aim was to analyze the effect of Myrmecodia pendans extract effect towards biofilm of Streptococcus sanguinis and Treponema denticola. Methods: Ant-nest plant was extracted using maceration technique. The obtained extract was diluted into five different concentrations using phosphate buffer saline (PBS). S. sanguinis and T. denticola ATCC 35405 were cultured in Brain Heart Infusion (BHI) broth, 48h, 37°C, anaerobic atmosphere and distributed into four 96 well-plate for 24h to form biofilm. Subsequently, the extract was distributed into the well that contained the mono-species and multispecies biofilm and then incubated for 1h, 3h, 6h and 24h. Chlorhexidine (0.2%) was used as positive control and BHI broth was used as negative control. The biofilm was stained using crystal-violet and measured by microplate reader with a wavelength of 490 nm. Data were statistically analyze using one-way ANOVA test and Post Hoc LSD test which p < 0,05 was set as significant difference. Result: The most effective concentrations to reduce mono-species biofilm were 100% in 1h incubation period for S. sanguinis (OD = 1,403 ± 0,019) and 24h for T. denticola (OD = 1,012 ± 0,037) and multispecies biofilm (OD = 0,984 ± 0,001) compared to negative control. Statistical analysis showed that ant-nest plant extract significantly reduced S. sanguinis, T. denticola and multispecies biofilm mass compared to negative control (p < 0,05). Conclusion: The ant-nest plant extract has inhibitory effects against S. sanguinis and T. denticola biofilm and it may be used as alternative for dental therapy. Future studies are needed to evaluate the potential of ant-nest plant extract in multispecies composed of other oral bacteria.